Evaluation of the Extracurricular Activities Administration Program in Improving Student Achievement at Madrasah Aliyah Miftahul Ulum Mukomuko - Andraini, Beta; Rahmayani, Lara (Al-Khair Journal: Management Education, 2025)
Abstract: Student achievement is still difficult to attain due to extracurricular coaches lacking competence in their respective fields. For example, the pramuka (scouting) program is sometimes assigned to individuals who do not have specific expertise in the field. This study aims to evaluate the administration program of extracurricular activities in improving student achievement at Madrasah Aliyah Miftahul Ulum Mukomuko. The research employs a qualitative descriptive method using the CIPP model (Context, Input, Process, Product). Data were collected through observation, interviews, and documentation. The results indicate that, in terms of context, extracurricular activities contribute to broadening students’ knowledge, enhancing skills, and shaping their character. Regarding input, the presence of competent coaches, supporting facilities, and a well-prepared activity curriculum are crucial factors for successful student achievement. In terms of process, the implementation of extracurricular programs runs fairly well, although it still faces challenges such as limited time, facilities, and supervision. In terms of product, the extracurricular program has a positive impact on improving student achievement, both academically and non-academically. Therefore, it can be concluded that the administration of extracurricular programs has the potential to enhance student achievement. It is recommended to continue developing and improving extracurricular programs at the madrasah.Keywords: Evaluation, Administration of Extracurricular Activities, Student Achievement. Abstrak: Prestasi siswa masih sulit diraih dikarenakan coach esktrakurikuler kurang kompeten dalam bidangnya. Contohnya kegiatan pramuka dibebankan kepada orang yang tidak punya keahlian khusus di bidang tersebut. Penelitian ini bertujuan untuk mengevaluasi program administrasi kegiatan ekstrakurikuler dalam meningkatkan prestasi siswa di Madrasah Aliyah Miftahul Ulum Mukomuko. Menggunakan metode kualitatif deskriptif model CIPP (Context, Input, Process, Product). Sumber data didapat melalui Observasi, Wawancara dan Dokumentasi. Hasil penelitian menunjukkan bahwa pada aspek konteks, kegiatan ekstrakurikuler berkontribusi dalam memperluas wawasan, meningkatkan keterampilan, serta membentuk karakter siswa. Pada aspek input, keberadaan pembina, fasilitas pendukung, serta kurikulum kegiatan yang memadai menjadi faktor penting dalam keberhasilan prestasi. Pada aspek proses, pelaksanaan kegiatan berjalan cukup baik meskipun masih menghadapi kendala seperti keterbatasan waktu, sarana, dan pengawasan. Pada aspek produk, program ekstrakurikuler terbukti memberikan dampak positif terhadap peningkatan prestasi siswa, baik prestasi akademik maupun prestasi Non Akademik. Dengan demikian, dapat disimpulkan bahwa program administrasi kegiatan ekstrakurikuler dapat meningkatkan prestasi siswa. Oleh karena itu, dapat disarankan untuk meningkatkan prestasi siswa. Maka, tingkatkanlah program kegiatan ekstrakurikuler di Madrasah.Kata Kunci: Evaluasi, Program Administrasi Kegiatan Ekstrakurikuler, Prestasi Siswa.